2007
DOI: 10.1176/ps.2007.58.3.365
|View full text |Cite
|
Sign up to set email alerts
|

Payeeship, Financial Leverage, and the Client-Provider Relationship

Abstract: Although payeeship provides important support and may enhance functional outcomes for the patient, decisions about using the mechanism for promoting treatment adherence should take into account the potential disruption to the client-provider relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…The sociodemographic and clinical profile of the subject on whom covert coercion was applied coincides with that described in the literature and corresponded to patients with psychosis and/or substance use disoders (Angell, Martinez, Mahoney & Corrigan, 2007;Appelbaum & Redlich, 2006;Burns, 2011;Monahan et al, 2001), severe and chronic illness (Appelbaum & Redlich, 2006;Burns et al, 2011;Molodynski, Rugkåsa & Burns, 2010;Monahan et al, 2005), poor insight (Gert, Culver & Clouser, 2006;Jaeger & Rossler, 2010), and dangerousness (Conrad et al, 2006;Monahan et al, 2001).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…The sociodemographic and clinical profile of the subject on whom covert coercion was applied coincides with that described in the literature and corresponded to patients with psychosis and/or substance use disoders (Angell, Martinez, Mahoney & Corrigan, 2007;Appelbaum & Redlich, 2006;Burns, 2011;Monahan et al, 2001), severe and chronic illness (Appelbaum & Redlich, 2006;Burns et al, 2011;Molodynski, Rugkåsa & Burns, 2010;Monahan et al, 2005), poor insight (Gert, Culver & Clouser, 2006;Jaeger & Rossler, 2010), and dangerousness (Conrad et al, 2006;Monahan et al, 2001).…”
Section: Discussionsupporting
confidence: 57%
“…Our professionals agreed when justifying the use of these strategies in their effectiveness and, in fact, several studies, which used economic incentives, found that they improved adherence Priebe, 2013); global functioning (Appelbaum & Redlich, 2006) and quality of life (Angell, Martinez, Mahoney & Corrigan, 2007). However, there are also authors who consider it negatively because of the possibility of stigma, loss of the therapeutic relationship and pose a barrier in treatment (Angell, Martinez, Mahoney & Corrigan, 2007;Swartz, Swanson & Hannon, 2003). More studies are needed to clarify the efficacy of them.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The potential benefits include improved housing stability (Luchins, Roberts, & Hanrahan, 2003;Rosenheck, Lam, & Randolph, 1997;Stoner, 1989); decreased inpatient hospitalization (Luchins et al, 1998), increased adherence to mental health treatment (Ries & Anne Comtois, 1997), and empowerment through supported decision making (Serowik, Bellamy, Rowe, & Rosen, 2013). The risks of having a representative payee include financial mismanagement by the payee (National Research Council, 2007), interpersonal conflict (Angell, Martinez, Mahoney, & Corrigan, 2007;Elbogen, Wilder, Swartz, & Swanson, 2008), perceived stigma (Elbogen et al, 2008), and loss of autonomy (Appelbaum & Redlich, 2006;Dixon, Turner, Krauss, Scott, & McNary, 1999;Elbogen, Soriano, Van Dorn, Swartz, & Swanson, 2005). The effects of being assigned a payee on substance use have not been consistent across locales.…”
Section: Introductionmentioning
confidence: 99%